FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PENYAKIT HIPERTENSI PADA LANSIA DI PUSKESMAS PRABUMULIH TIMUR KOTA PRABUMULIH - Fatimah, Fatimah; Sulastri, Sulastri; Krisnawati, Reni (Journal Safety and Healthty, 2024)
Health development aims to increase awareness, willingness, and ability to live healthy for everyone in order to realize the highest degree of public health, as an investment for the development of socially and economically productive human resources. Increasing life expectancy. The purpose of this study was to determine the relationship between genetics, smoking habits and stress with the incidence of hypertension. The design of this research is Cross Sectional. The population in this study were all respondents who visited the Prabumulih Timur Health Center, Prabumulih City, totaling 137 patients, with a sample of 58 respondents, the sampling technique was Acidental sampling. Analysis of the results of the study using Chi-Square (bivariate) with = 0.05, this study concluded that there is a significant relationship between genetics, smoking habits, stress, simultaneously with the incidence of hypertension in the elderly at Prabumulih Timur Health Center, Prabumulih City. Suggestions for this research are expected to always improve health services so that they can provide quality services, especially to be further improved in providing information to family members and providing counseling about prevention in patients with hypertension.